2013 Physics Education Research Conference Proceedings 2014
DOI: 10.1119/perc.2013.pr.031
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Learning Assistants: The Impact of an Authentic Teaching Experience on Undergraduate Physics Majors

Abstract: UNCG has an innovative Learning Assistant (LA) program, in which upper-class undergraduate physics majors teach laboratory sections of the introductory calculus-based physics sequence. The lecture section's professor provides supervision and determines the overall learning objectives and structure of the labs, but the team of LAs develop the detailed lesson plans, write up all handouts and quizzes, conduct the lab sessions, and evaluate student work. This gives the LAs a genuine voice in planning and teaching,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…While a substantial amount of work has investigated students leaving STEM, there has been less work that has focused on leaving physics, specifically. The work that has been done supports the broader work in STEM and has identified better performance [8], use of teaching reformations [10,22,23,31], and increased interest [24] as all having had positive effects on the retention of physics majors. Aiken and Caballero [8] found that students' performance in introductory physics and calculus courses and when these students take these courses was important to completing a physics degree [8].…”
Section: A Leaving Stem Literaturementioning
confidence: 68%
See 2 more Smart Citations
“…While a substantial amount of work has investigated students leaving STEM, there has been less work that has focused on leaving physics, specifically. The work that has been done supports the broader work in STEM and has identified better performance [8], use of teaching reformations [10,22,23,31], and increased interest [24] as all having had positive effects on the retention of physics majors. Aiken and Caballero [8] found that students' performance in introductory physics and calculus courses and when these students take these courses was important to completing a physics degree [8].…”
Section: A Leaving Stem Literaturementioning
confidence: 68%
“…Additionally, increased retention has been linked to reformations in teaching and learning [11,17,21]. Physics Education Research (PER) has also explored this topic finding similar results [8,10,[22][23][24]. This section summarizes the literature that has explored these themes.…”
Section: A Leaving Stem Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…The questionnaire consisted of seven Likert-type scales soliciting agreement or disagreement with various statements about the lab instructors' efficacy, and an open-ended response box inviting "any additional thoughts or comments about the lab instructors." For all seven scales, students were asked to select "strongly disagree" (1), "disagree", (2), "neutral" (3), "agree" (4), or "strongly agree" (5).…”
Section: Data Collectionmentioning
confidence: 99%
“…It has been designed to provide participants with as authentic a teaching experience as possible, in the hopes that this will increase their understanding of and interest in a possible teaching career. (A companion paper in this proceedings volume explores the impact of the program upon LA participants [5]. )…”
Section: Introductionmentioning
confidence: 99%